A STUDY OF ALIENATION IN KAFKA’S THE METAMORPHOSIS AS A MORAL GUIDE FOR THE NEW GENERATION - Weam Majeed Alkhafaji (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Modern world can learn a lot from Franz Kafak`s The Metamorphosis story. It deeply exposed alienation theme, and employed it as a vehicle to show the fault of modern man. This novel was published at a period when world was only responding to the effects of the industrial revolution. Employees had to change social interactions within the workplace to adapt to the current power system. Individuals struggled to fulfill the pressures of work and personal life and were exhausted. Gregor’s alienation was a tragic consequence of the unsustainable socio-economic system of industrialization, contributing to his separation from social principles. This paper investigates the effects of separation of individuals who as a result have not only alienated themselves from their society but they lost their identity as well as moral values. It also focuses on the economic, political and financial issues that have changed them entality of young people from a source of benefits to a source of risks. To do so, my paper is going to consider Kafka`s The Metamorphosis as a raw material to examine the concept of alienation of the contemporary man.